Verifikasi Model Sistem Pengelolaan Tegakan Hutan Alam Setelah Penebangan dengan Tebang Pilih Tanam Indonesia (TPTI) - Indrawan, Andry (Institut Pertanian Bogor (IPB University), 2003)
Lowland Tropical Rain Forest in Forest concession (HPH) PT. Inhutani II, Stagen Pulau Laut, South Kalimantan, and in forest concession PT. Ratah Timber Co, are climax forest under dynamic equilibrium, which are dominated by tree species from Dipterocarps family. Mechanical logging which is conducted in forest concession area will result in the formation of forest with certain composition and structure. Recovery of the forest is left to proceed naturally and will take a certain amount of time, and will affect the next duration of rotation. From the simulation result which were made on the basis of data from permanen plot in area of PT. Inhutani II, it was found that respond of simulation or respond of logged over natural forest management system in permanen plot, revealed that cutting cycle I after logging require ± 24 years time, whereas cutting cycle II require ± 37 years time. Model obtained from simulation result which were made on the basis of data obtained from permanen plot in area of PT. Inhutani II, is used for data which were obtained from non permanen plot at forest concession area of PT. Ratah Timber Co. Respon of simulation from forest concession of PT. Ratah Timber Co reveal that cutting cycle I after logging require ± 30 years time, whereas cutting cycle II require ± 43 years of time. This Phenomena imply that cutting cycles, are not always constant and will change in line with the composition and structure of logged over natural forest and their development with time.